К вопросу о рецепции права в российской консервативной правовой идеологии - Vasilyev, Anton (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2017)
The article is devoted to the phenomenon of law reception in the interpretation of the Russian conservatism. The attitude of Russian conservatives towards adopting foreign law was dictated by the dominance of organic methodology in conservatism. The organicism of the conservative legal ideology assumed with the inevitability of the development of law at the expense of internal, immanent factors and actually denied the possibility of reception of law. The evolution of law for the Russian conservatives was conceived in two forms: the spiritualization of old forms of law and the immanent transformation of existing legal institutions. In adopting foreign law, Russian conservatives saw the danger of an invasion of the cultural, spiritual sphere of legal reality.